Pesan Moral Film Kinari Folklore Desa Tempur. (Analisis Semiotika Roland Barthes) - Rivai, Muhamad Anang; Asiyah, Siti; Kurniawan, Fajar Adhi (Prodi KPI FDPM IPMAFA Bekerjasama dengan Mafa Press IPMAFA Pati, 2025)
The film Kinari is a film produced by Ladamif films from Jepara in 2023, raises a unique folklore that tells the story of the Tempur Village chronicle. The story of this village comes from the Tempuran River. The battle river is a meeting two currents used for bathing rituals or cleansing the soul of the body the ancestors. This tradition certainly contains a moral message that wants to conveyed to the community so that the objectives of this study are to provide education to maintain traditions and preserve nature in the surrounding environment. Through qualitative research using Roland Barthes' semiotic analysis, the results of this research can be seen from eating denotations, meanings, connotations and myths so that the moral message conveyed in the film Kinari is the moral message of man having a relationship with his god, the moral message of man having a relationship with himself and the moral message of human relations with others.